Pre- and post-conditional inhibition of prolyl-4-hydroxylase domain enzymes protects the heart from an ischemic insult - Vogler, Melanie; Zieseniss, Anke; Hesse, Amke R.; Levent, Elif; Tiburcy, Malte; Heinze, Eva; Burzlaff, Nicolai; Schley, Gunnar; Eckardt, Kai-Uwe; Willam, Carsten; Katschinski, Doerthe M. (Pflügers Archiv: European Journal of Physiology, 2015)
Several genetically modified mouse models implicated that prolyl-4-hydroxylase domain (PHD) enzymes are critical mediators for protecting tissues from an ischemic insult including myocardial infarction by affecting the stability and activation of hypoxia-inducible factor (HIF)-1 and HIF-2. Thus, the current efforts to develop small-molecule PHD inhibitors open a new therapeutic option for myocardial tissue protection during ischemia. Therefore, we aimed to investigate the applicability and efficacy of pharmacological HIF? stabilization by a small-molecule PHD inhibitor in the heart. We tested for protective effects in the acute phase of myocardial infarction after pre- or post-conditional application of the inhibitor. Application of the specific PHD inhibitor 2-(1-chloro-4-hydroxyisoquinoline-3-carboxamido) acetate (ICA) resulted in HIF-1? and HIF-2? accumulation in heart muscle cells in vitro and in vivo. The rapid and robust responsiveness of cardiac tissue towards ICA was further confirmed by induction of the known HIF target genes heme oxygenase-1 and PHD3. Pre- and post-conditional treatment of mice undergoing myocardial infarction resulted in a significantly smaller infarct size. Tissue protection from ischemia after pre- or post-conditional ICA treatment demonstrates that there is a therapeutic time window for the application of the PHD inhibitor (PHI) post-myocardial infarction, which might be exploited for acute medical interventions.
EVALuna2:3781